Konsensualne sposoby zakończenia procesu w sprawach o wykroczenia - Liżyńska, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The noticeable increase in the importance of consensus in criminal proceedings including cases of petty offences, prompted reflection on the institutions allowing legal proceedings to be terminated without full evidence investigation. Undoubtedly, this simplification affects the pace of legal proceedings, and hence their economy. However, we cannot also overlook its influence on the more efficient implementation of the compensation function of a trial, as well as the greater subjective acceptability of the judicial decision by the parties of legal proceedings. The author of the following paper analyzes institutions of consensual resolving of disputes in legal proceedings concerning petty offences, pointing to the pros and cons of applying such a solution.
Keywords: konsensualne sposoby; sprawca; prawa; mediacja